Why public policies fail: Policymaking under complexity - Bernardo Mueller (EconomiA, 2020)
The failure of public policies is ubiquitous. This paper ascribes this failure to the complex system nature of public policies. A key characteristic of complex systems is that they cannot be closely controlled or predicted. Yet the traditional approach to public policy is fundamentally based on both control and prediction, as it proceeds by comparing the expected costs and benefits of a postulated set of alternatives. In this paper I provide five pathologies of complex systems and show how they cause the failure of the traditional approach. If a public policy is recognized as taking place within a complex system, it is necessary to use instruments that can work within those informational and epistemological constraints. I provide several examples of the types of policies that meet these demands. But when dealing with complex systems, even with appropriate instruments it is nevertheless necessary to adjust the expectations of what can realistically be achieved.
Keywords: D8; D04; D78; H5; 330; Complex systems; Complexity; Policy failure; Public policy